The image of St Louis - Kauffmann, M (Centre for Late Antique and Medieval Studies, King's College London, 1993)
The earliest surviving full pictorial cycle of the Life of St Louis, probably dating from the early years of the fourteenth century, is found in the Lady Chapel of the Benedictine abbey church of the Trinity at Fecamp in Normandy. The interest of this glass lies not only in the early witness it bears to the cult of St Louis, who was canonized in 1297, but also in the company it keeps. The glass in the chapel also includes a cycle of the Life of Edward the Confessor, the English royal saint canonized in 1161. Edward had spent his youth in exile at Fecamp, and was commemorated in the liturgy of the abbey. Whilst this may be sufficient in itself to explain Edward's presence here, the juxtaposition of Edward and Louis may also re- flect the marriage in 1308 of Edward II of England to Isabella, the daughter of Philip IV of France. Whatever the circumstances, it may help us to examine the cult of St Louis in the light of his English counterpart. This essay will focus on some of the tensions and contradictions inherent in the image of these royal saints.